Dealing with dictators dilemmas of U.S. diplomacy and intelligence analysis, 1945-1990 - edited by Ernest R. May. (Cambridge MIT Press, 2006)
The United States continues to proclaim its support for democracy and its opposition to tyranny, but American presidents often have supported dictators who have allied themselves with the United States. This book illustrates the chronic dilemmas inherent in US dealings with dictators under conditions of uncertainty and moral ambiguity.Dealing with Dictators offers in-depth analysis of six cases: the United States and China, 1945-1948; UN intervention in the Congo, 1960-1965; the overthrow of the Shah of Iran; US relations with the Somoza regime in Nicaragua; the fall of Marcos in the Philippines; and US policy toward Iraq, 1988-1990. The authors' fascinating and revealing accounts shed new light on critical episodes in US foreign policy and provide a basis for understanding the dilemmas that US decision makers confronted. The chapters do not focus on whether US leaders made the "right" or "wrong" decisions, but instead seek to deepen our understanding of how uncertainty permeated the process and whether decision makers and their aides asked the right questions. This approach makes the book invaluable to scholars and students of government and history, and to readers interested in the general subject of how intelligence analysis interacts with policymaking.
Includes bibliographical references and index.
Keywords: Dictators--Case studies